Rags to riches; Real love; From guns to God; Just got lucky [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Summary: Portrays the real life stories of Cyrus Aparri, Mari Kaimo and Enchang Agudo, Binbong Crisologo, Manila Mayor Alfredo Lim and other.
Contents: Rags to riches (12 min.) -- Real love (10 min.) -- From guns to God (13 min.) -- Just got lucky (15 min.)
VHS.
Keywords: Aparri, Cyrus -- Interviews; Agudo, Enchang -- Interviews; Crisologo, Bingbong -- Interviews; Lim, Alfredo -- Interviews